Studies in industrialization: Nigeria and the Cameroons - Wells, Frederick Arthur; Warmington, Allan (London: Published for the Nigerian Institute of Social and Economic Research [by] Oxford University Press, 1962)
This studies examines industrialization as a concept with emphasize to Nigeria and Cameroons.
Includes bibliography.
asm; 27/02/19
Loans
Keywords: Industrialization; Economic development; Nigeria; Cameroons